1974
DOI: 10.1530/jrf.0.0380387
|View full text |Cite
|
Sign up to set email alerts
|

Antitesticular and Antifertility Activity of a Pipecolinomethylhydroxyindane in Rats

Abstract: Treatment with dl-6-(N-\g=a\-pipecolinomethyl)-5-hydroxyindane maleate (PMHI) has been found to depress testicular weight and interfere with spermatogenesis and fertility in the male rat. At equal doses by weight, PMHI caused a greater reduction in testicular weight than WIN 18446, nitrofurazone, methallibure and diethylstilboestrol, but lesser reductions in seminal vesicle and ventral prostate weights than were obtained with the two antigonadotrophic compounds, methallibure and diethylstilboestrol. Doses of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1974
1974
1991
1991

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Sterility ensued from the 5th week and persisted to the termination of the experiment 20 weeks after dosing. The antitesticular activity of DL-6-(N-a-pipecolinomethyl)-5-hydroxyindane maléate (PMHI) in the rat and other species has been described (Boris, Ng & Hurley, 1974;Boris, DeMartino & Cox, 1974). These studies also indicated that treatment with PMHI for 21 days caused sterility in male rats, and that the reversibility of the antifertility effect depended on the dose which had been given.…”
mentioning
confidence: 99%
“…Sterility ensued from the 5th week and persisted to the termination of the experiment 20 weeks after dosing. The antitesticular activity of DL-6-(N-a-pipecolinomethyl)-5-hydroxyindane maléate (PMHI) in the rat and other species has been described (Boris, Ng & Hurley, 1974;Boris, DeMartino & Cox, 1974). These studies also indicated that treatment with PMHI for 21 days caused sterility in male rats, and that the reversibility of the antifertility effect depended on the dose which had been given.…”
mentioning
confidence: 99%
“…In the rat, PMHI caused a relatively greater reduction in testicular weight than other antigonadal agents such as nitrofurane, methallibure and diethylstilbestrol, and appears to act directly upon the testis leading to destruction of the spermatogenic epithelium [2]. Furthermore, a single oral dose of the indane derivative caused loss of spermatogenesis in rats without drastic effects upon the weights of the accessory sex organs [3].…”
Section: Introductionmentioning
confidence: 93%
“…[91][92][93] It is active in rats by oral route. Dose for dose, it causes greater reduction in testicular weight than WIN 18446, nitrofurazone, methallibure, and diethylstilbestrol (DES), but less reduction in seminal vesicle and ventral prostate weight as produced by antigonadotrophic agents methallibure and DES.…”
Section: Miscellaneous Compounds Dl-6-(n-a-pipecolinomefhyl) -5-hydrmentioning
confidence: 99%